Social-based learning and leadership in school: conflict management training for holistic, relational conflict resolution - Vinokur, Eli; Yomtovian, Avinoam; Marom, Marva Shalev; Itzchakov, Guy; Baron, Liat (Frontiers in Social Psychology, 2024)
Navigating conflicts is crucial for promoting positive relationships between pupils, teachers, and parents. The objective of this paper is to present Social-Based Learning and Leadership (SBL), an innovative approach to group dynamics and conflict resolution within the school setting, aiming to foster meaningful relationships and personal and social growth. The methods of SBL focus on group evolution by navigating conflicts rooted in higher needs while balancing the interplay of separation and connection. It proactively embeds prosocial values and conduct into the school culture, with teachers prioritizing the wellbeing of others, fostering shared problem-solving, and positive feedback amid conflicts. Teachers acquire tools to transform the classroom into a “social laboratory” and construct meaningful partnerships with parents. Practical conflict management within the SBL framework involves dynamic group discussions, shifting from other blaming to accountability, and reflective group introspection. Experiential learning through crafted case studies and role-plays enhances students' conflict management skills by fostering perspective-taking and inclusiveness. We conducted a qualitative case study in an SBL training in a school from 2020 to 2023. These conflict management processes allow the school community to reimagine conflict as an invaluable educational opportunity, equipping pupils with essential soft skills for navigating the challenges of the 21st century.